Studying International Experience In The Field Of Formation Of Promotion Mechanisms In The Field Of Strengthening Scientific Potential (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
Research relevance: To contribute to the scientific discourse of improving higher education’s current state of scientific potential, in order to bring it to a higher level. Research study: Methods of obtaining articles on strengthening the potential of domestic science compared to world level.Limitations of the study: The study was designed only for a specific country. More empirical studies are needed to carry out more general study.Practicality of the study: There is a huge impact of science to the modern economy.Originality and scientific novelty of the study: The study is aimed at producing new results in this direction.Keywords: scientific potential of the country, scientific environment, science-finance closed loop, plagiarism and database systems.